1979
DOI: 10.1080/15298667991429778
|View full text |Cite
|
Sign up to set email alerts
|

A six-year follow up study for evaluation of the 85 dBA safe criterion for noise exposure

Abstract: This study included 114 workers who have been exposed to noise levels of 78 to 91.4 dBA and followed over a six year period. Workers exposed to nose levels up to 85 dBA eight hours daily for six days per week and for twelve years showed a slightly higher (1%) hearing impairment than the corresponding control subjects. Impairment of hearing among workers exposed to higher noise levels was 9.6%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…This level is supposed to inhibit hearing impairments of workers (Moselhi et al, 1979). Even the ILO (International Labour Organization) indication agree with this.…”
Section: Introductionsupporting
confidence: 52%
“…This level is supposed to inhibit hearing impairments of workers (Moselhi et al, 1979). Even the ILO (International Labour Organization) indication agree with this.…”
Section: Introductionsupporting
confidence: 52%
“…It was demonstrated that noise-induced hearing loss occured on textile workers as well 2,14,15) . An evident hearing loss occurs also in the textile workers, especially who are exposed to noise at 95 dB (A) or more when compared to the group that are not exposed to any noise 2) .…”
Section: Discussionmentioning
confidence: 99%
“…Moselhi et al 1979 Hong Kong Five industries: weaving, bottling, metal working, spinning, airport Leq (8-hour time-weighted average, dBA): weaving 102; bottling 94; metal working 96; spinning 97; airport [80][81][82][83][84][85][86][87][88][89][90] Compared to controls, noiseexposed workers had significantly higher thresholds in most age groups and in all five industries, closely matching predicted values.…”
mentioning
confidence: 99%